2007
DOI: 10.1016/j.jcrs.2006.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Variant of the big bubble technique in deep anterior lamellar keratoplasty

Abstract: We describe a variant of the big-bubble technique that involves placement of a stromal corneal nick and nontraumatic intrastromal insertion of a blunt cannula following anterior lamellar keratectomy. The goal of this technique is to reduce the risk for intraoperative corneal perforation and to obtain a large air bubble between Descemet's membrane and the corneal stroma. Deep anterior lamellar keratoplasty is easier and safer with this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…This surgical technique is well accepted because it is not an intraocular procedure and has several advantages over PKP, such as preservation of endothelium, reduced long-term use of steroids, and rapid visual rehabilitation. 7,15,23,25,27 The safety and efficacy of DALK using the Melles et al technique, 27 the big-bubble technique, 15 or variations of the big-bubble technique 35,36 in moderate to advanced keratoconus cases have been shown in several studies. In the current study, the UDVA and CDVA significantly improved in eyes that had DALK surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This surgical technique is well accepted because it is not an intraocular procedure and has several advantages over PKP, such as preservation of endothelium, reduced long-term use of steroids, and rapid visual rehabilitation. 7,15,23,25,27 The safety and efficacy of DALK using the Melles et al technique, 27 the big-bubble technique, 15 or variations of the big-bubble technique 35,36 in moderate to advanced keratoconus cases have been shown in several studies. In the current study, the UDVA and CDVA significantly improved in eyes that had DALK surgery.…”
Section: Discussionmentioning
confidence: 99%
“…He used special forceps and a golf club-shaped diamond knife for hooking the stromal fibers at the trephination wound to expose the DM. Fournié et al 12 introduced a technique that forms an air bubble at the DM-stroma interface by making a corneal stromal nick after lamellar dissection and injecting air via a blunt cannula through the stromal nick. They refilled the airfilled cavity with viscoelastic material, they benefitted from the advantages of an extraocular procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that using a cannula to inject air provides the highest rate of successful BB accomplishment. Fourniè et al indicated a BB success rate of 76.9% in a study of 13 eyes [22] . Sarnicola and Toro reported BB formation in 86% of cases in a study of 28 eyes [21] .…”
Section: Cannula Big Bubblementioning
confidence: 94%